Build Your Continuous Integration and Continuous Delivery Pipeline for Salesforce Platform - Kokku, Rishitha (International Journal of Computing and Engineering, 2020)
Salesforce is a CRM platform offering its customers point and click options to build their applications. This work for small scale industries and organizations whose operations are limited. Salesforce is very different to other technology stacks and hence will be its DevOps implementation. Companies when trying to expand their business cannot achieve their requirements with configurations and often need customizations and code development. Deployment of this code is achieved by implementing a CICD process which is different from DevOps practices of other technologies. Salesforce offers a built-in deployment option called Changesets to migrate the changes between environments. This guide talks about what is Changesets and what are the other ways to implement Salesforce DevOps